131 A MORE UNIQUE THAN RARE MYOPERICARDITIS - A CASE REPORT. (15th December 2022) - Berghi, Razvan; Merlo, Marco; Carriere, Cosimo; Sinagra, Gianfranco
Abstract: A 33yo man, ex-convict, with a history of IV substance abuse, without previous cardiological history, was admitted at our emergency department in the clinical context of an acute pericarditis, intermittent fever in the last 10 days and non-itchy maculo-papular erythema of palms and thorax. EKG documented a diffuse ST-segment elevation, chest X-rays revealed a bilateral pleural effusion and echocardiography documented a normal biventricular morphology and function, normal valvular function, and a circumferential pericardial effusion (14mm). The patient was admitted at our Cardiology Unit after a negative PCR SARS-CoV-2 test. Blood chemistry showed elevated WBC count with an important neutrophilia (24.000/mm3; 90% neutrophils), elevated TnI-HS (236 ng/L; n.v. <18 ng/L), elevated C-reactive protein (340 mg/L; n.v. < 5mg/L). A classic anti-inflammatory therapy was set up with indomethacin + colchicine with little clinical benefit. Blood cultures, bacterial serology (i.e., Tubercolosis, T.gondii, Syphilis, Leptospirosis) and viral serology (i.e., HIV, HCV, HBV, EBV, HSV) resulted negative. However, an empirical antibiotic coverage was set up: sequentially with Piperacillin/Tazobactam, Vancomycin, Linezolid and Ceftriaxone. None of the antibiotics improved patient's clinical status. On the contrary, the patient developed an allergic reaction to Vancomycin and Linezolid. All autoantibodies tested resulted negative. After 10 days of hospitalization, the patient's clinical status continued to deteriorate. The intermittent fever (max 41°C) was not responsive to any treatment. The evanescent skin rash had spread to the whole body and was concomitant with the fever peaks. The indexes of inflammation were rising (C-reactive protein 400 mg/L) and so were the WBC count (36.000/mm3). The patient lost weight (-8kg), developed hand and feet arthralgia, diffuse myalgia, painful retronucal lymph nodes, pharyngodynia and abdominal pain. An abdominal echography and CT were performed with evidence of mild abdominal effusion and splenomegaly. Hepatic cytolysis indices began to rise (AST 100 U/L; ALT 150 U/L; LDH 385 U/L). At that point, on the basis of Yamaguchi's Criteria, we suspected our patient could be affected by Adult-onset Still's disease (AOSD) with an initial stage of hemophagocytic lymphohistiocytosis (HLH). Prednisone (IV 2 mg/kg/die) was administered for 72h with an incomplete clinical and biochemical response (C-reactive Protein 180 mg/L). Subsequently, Anakinra (SC 100 mg/die) was administered with a complete clinical response in less than 72h. AOSD is very uncommon. The annual incidence is 0.16/100.000 with an equal distribution between sexes. HLH have been observed in 15% of patients, meanwhile myopericarditis is a rare complication. Although rare, it is fair to know and consider AOSD in the complicated and tricky diagnostic process of myopericarditis. A noteworthy point of this case report is the extreme efficacy of Anakinra in contexts of systemic inflammation and myopericarditis. A point still to be clarified concerns the duration of the treatment and the down-titration of Anakinra in these complicated contexts.